Huperzine A: a natural acetylcholinesterase inhibitor with multifunctional neuroprotective effects - Suvaiv; Kuldeep Singh; Syed Misbahul Hasan; Arun Kumar; Abdullah khan; Mo. Shahanawaz; Syed Mehdi Hasan Zaidi; Kausal Verma (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background Huperzine A, a naturally derived compound, has garnered interest for its capacity to inhibit cholinesterase with multifaceted neuroprotective effects and is obtained from Huperzia serrata (Chinese club moss plant). This review highlights its pharmacological potential in the treatment of neurodegenerative disorders, particularly Alzheimer’s disease (AD). Huperzine A was used in various neurological conditions in traditional Chinese treatments. Findings Acetylcholinesterase is responsible for the breakdown of acetylcholine, a neurotransmitter critical for cognitive functions such as memory, learning, and attention. Huperzine A exhibits neuroprotective effects by preserving acetylcholine levels, and also offers antioxidant and anti-inflammatory benefits. These pharmacological actions suggest a potential role in modifying disease progression in AD and vascular dementia (VD). Although preclinical and clinical studies have demonstrated promising cognitive benefits, discrepancies in outcomes still exist. While considered safe at therapeutic dosages, excessive intake may lead to adverse effects, e.g., nausea, diarrhea, and muscle cramps. Conclusion Research on its effectiveness in various neurological conditions is ongoing, and its use should be approached with caution and professional guidance.